Knowledge of HIV Transmission and Factors Related to the Incidence of HIV/AIDS in Adolescents in Indonesia - Ruri Kharisma Fitriani1 , Lutfi Agus Salim2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Adolescents are vulnerable to various health risk, especially caused by social interactions, like juveniledelinquency and drug abuse, premarital sex and unwanted pregnancy to an increased incidence of sexuallytransmitted infections including HIV/AIDS. The number of AIDS cases in students is 282 cases, morethan double prostitutes who are 137 cases. The purpose of this study is to find out how is the knowledge ofyoung people about HIV / AIDS, how HIV are transmitted and what are the factors that associated with HIVincidence in adolescents in Indonesia. This paper uses a qualitative method with literature study or libraryresearch, then data obtained is analyzed using descriptive analysis methods. HIV/AIDS can be transmittedthrough bodily fluids contact and is related to several factors such as gender, family factors, communityenvironment, technology and communication. Cooperation of all sectors, parents, social institutions, andsociety to support government programs for HIV/AIDS-free Indonesia.